Perceived self-image in adolescent idiopathic scoliosis: an integrative review of the literature - Maria Isabel Bonilla Carrasco; Maria Carmen Solano Ruiz (SciELO, 2014)
Objective: To learn about the experiences of adolescents diagnosed with idiopathic scoliosis. Method: Integrative review of the literature published within a specified time frame. Results: For both sexes, the predominant clinical symptom of this condition appears to be the negative effect that the deformity exerts on perceived self-image. Quantitative studies used numerical scores to assess perceptions of body image but did not analyse emotional aspects. Patients treated surgically were found to have a better self-image than patients treated with a brace. Quality of life was improved by a reduction in the magnitude of the curve. Conclusion: Spinal deformity exerts a psychological effect on adolescent girls.